Efeito da Biochanina A sobre alterações imunometabólicas induzidas em camundongos ovariectomizados obesos - Aragão, Jéssica Maria Dantas Araújo (2021)
The absence of estrogen during menopause accompanies the increased propensity to develop obesity and other metabolic disorders. Adipose tissue (AT) is an immunologically active organ, which during the healthy state presents a profile of anti-inflammatory cytokines released by immune cells that ensure tissue homeostasis, such as alternatively activated macrophages (M2) and eosinophils. Increased adiposity is the critical point in a chain of pathophysiological events that include chronic low-grade inflammation, dyslipidemia, insulin resistance, and lipotoxicity in several organs, including liver, muscle, and kidney. Peroxisome proliferator-activated receptor gamma (PPARƴ) agonists, such as the phytoestrogen Biochanin A (BCA), have shown important effects on these pathologies caused by lipotoxicity. Thus, the study aimed to investigate the effects of BCA treatment on immunometabolic alterations occurring after ovariectomy (OVX) and high-fat (HFD) diet-obesity induced. For this purpose, 17-20 weeks old female C57Bl/6 mice were ovariectomized or not (SHAM), and after 2 weeks they were fed with HFD or standard diet (SD) for the subsequent 9 weeks. After this period, the daily BCA administration (2 mg/kg; intraperitoneally for 30 days) was started in the group of animals OVX DH BCA, or administration of the vehicle (DMSO 0.5% in saline), in all other groups. For statistical analysis, the one-way or two-way analysis of variance (ANOVA) test and Tukey's post-test were applied. Results were considered significant when p<0.05. It was shown that BCA produced anti-inflammatory effects on AT, compared to untreated animals, reducing weight gain, adiposity, crown-like structures (CLS), predictors of tissue inflammation; increased the amount of antiinflammatory cytokines IL-5, an important eosinophils recruiter, and IL-10, without changing the pro-inflammatory IL-6 and IL1-β, in ovariectomized obese animals. BCA did not reverse inflammation in the liver, kidney, or change hematological parameters, however, it showed a modest effect in muscle by reducing the enzyme N-acetylglucosaminidase (NAG) activity. Thus, the data set presented suggests that the low dose of 2 mg/kg of BCA via i.p was not sufficient to reverse the inflammation generated in these organs. Despite this, the effects on IL-5 secretion, CLSs formation and adiposity may help researches that aim to understand the eosinophils role and the BCA effect on the change in the inflammatory profile in AT during the development of obesity. Furthermore, phytoestrogen may represent an important promising agent for controlling the inflammation generated during menopause obesity.